2020
DOI: 10.1097/pcc.0000000000002272
|View full text |Cite
|
Sign up to set email alerts
|

Daily Practice of Mechanical Ventilation and Weaning in Turkish PICUs: A Multicenter Prospective Survey

Abstract: Objectives: To investigate conventional mechanical ventilation weaning characteristics of patients requiring conventional mechanical ventilation support for greater than 48 hours within the PICU. Design: The prospective observational multicenter cohort study was conducted at 15 hospitals. Data were being collected from November 2013 to June 2014, with two designated researchers from each center responsible for follow-up and data entry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…(1) recovery from primary disease-causing mechanical ventilation, (2) adequate spontaneous breathing and effective coughing, (3) increasing consciousness, (4) hemodynamic stability with minimal vasoactive support, (5) oxygenation index <6, (6) lack of excessive tracheal secretion (less need for endotracheal suctioning), (7) adequate gas exchange with positive end-expiratory pressure (PEEP) < 8 cm H 2 O and fractional oxygen concentration (fiO 2 ) < 60%. The exclusion criteria were as follows:…”
Section: Population and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) recovery from primary disease-causing mechanical ventilation, (2) adequate spontaneous breathing and effective coughing, (3) increasing consciousness, (4) hemodynamic stability with minimal vasoactive support, (5) oxygenation index <6, (6) lack of excessive tracheal secretion (less need for endotracheal suctioning), (7) adequate gas exchange with positive end-expiratory pressure (PEEP) < 8 cm H 2 O and fractional oxygen concentration (fiO 2 ) < 60%. The exclusion criteria were as follows:…”
Section: Population and Study Designmentioning
confidence: 99%
“…The use of invasive mechanical ventilation (IMV) with positive pressure is widespread in pediatric intensive care units (PICUs), with at least one-third of children being mechanically ventilated. 1,2 Prolonged IMV is associated with ventilator-related injury, increased nosocomial infection risk, longer sedation requirement 3 and diaphragmatic atrophy. 4 Ultimately, children should be weaned from the ventilator once the clinical condition improves.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive mechanical ventilation (IMV) with positive pressure is widespread in pediatric intensive care units (PICUs), with at least one-third of children being mechanically ventilated. 1,2 . Prolonged IMV is associated with ventilator-related injury, increased nosocomial infection risk, longer sedation requirement 3 and diaphragmatic atrophy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Pressure-controlled ventilation modes (assist/control or synchronized intermittent mandatory ventilation) are frequently preferred modes in pediatric mechanical ventilation practice. 4 , 5 Anaesthesiologists’ choice of pressure-controlled modes due to the inability of delivering low tidal volumes with conventional (old) anaesthesia machines during pediatric anaesthesia procedures seems to be the origin of this practice. 6 , 7 The studies conducted in pediatric intensive care units in Argentina and Italy in 2003 and 2007 showed that PRVC mode usage was not common in their daily pediatric intensive care practice.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 The studies conducted in pediatric intensive care units in Argentina and Italy in 2003 and 2007 showed that PRVC mode usage was not common in their daily pediatric intensive care practice. 8 A recent study by Tekgüç et al 4 shows that pressure-controlled ventilation modes have been used more frequently in the weaning period than PRVC (almost 5%) in daily pediatric critical care practice in Turkey. The objective of this study is to present our clinical experience of using PRVC and PC ventilation modes in children.…”
Section: Introductionmentioning
confidence: 99%